Mapping Research Trend of Jurnal Bina Praja: A Bibliometric Review Between 2012 and 2021 - Rahmah, Mutia; Hamdi, Muchlis (Research and Development Agency Ministry of Home Affairs, 2022)
This study intend to see the trend of articles published in Jurnal Bina Praja through co-authorship dan co-occurrence analysis by describing the citation trend, most cited articles, top productive author, most collaborated author, most frequently keyword appeared, the latest, and the densest keyword of the journal. This study used several applications for collecting and analyzing the data, namely Publish or Perish for searching the literature, Mendeley for completing the metadata, and VOSviewer for building the visualization and analysis. The result of this study denotes there are 273 articles published online in Jurnal Bina Praja from 2012 volume 4 number 1 to 2021 volume 13 number 2. Based on this mapping, there has been a significant increase in citations from 2017 to 2020. The year 2020 was the year in which this journal obtained the highest number of citations, namely 266 citations compared to the previous year, which was only 162 citations. The most cited article was the one written by Saksono in 2012 entitled